2021
DOI: 10.1111/ddg.14336
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient dermatology: Where are we headed? A nationwide population‐based study of Spain from 2006 to 2016

Abstract: Summary Background and objectives Information about hospital admissions for skin diseases is restricted to studies describing admissions to single centers, to specific wards, or only for a few diagnoses, and there is no information about the outcomes between different wards. The aim of this research is to describe hospital admissions due to dermatological diseases. Patients and methods Cross‐sectional study of hospital discharges at Spanish hospitals. Discharges were assumed to be the same as admissions. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[12] Within our hospital, consultations from other departments predominate the inpatient workload for our dermatologists, as observed in other countries. [11] Unlike in other studies, [15,16] the discipline of surgery, mostly through the plastic and reconstructive department, had the greatest need for the dermatology consultation service. This may be explained by common diseases encountered or managed by dermatology and plastic surgery, such as cutaneous malignancies and keloids.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[12] Within our hospital, consultations from other departments predominate the inpatient workload for our dermatologists, as observed in other countries. [11] Unlike in other studies, [15,16] the discipline of surgery, mostly through the plastic and reconstructive department, had the greatest need for the dermatology consultation service. This may be explained by common diseases encountered or managed by dermatology and plastic surgery, such as cutaneous malignancies and keloids.…”
Section: Discussionmentioning
confidence: 95%
“…As expected, >90% of all dermatology inpatient services are offered in the consultation service, with only 3.8% being managed as dermatology inpatients. [11] The median (IQR) age of the study population was 42.0 (28.0 -58.0) years. Dermatology-admitted inpatients were younger than patients managed in the consultation service, with median ages of 37 years and 42 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…admitted to dermatology wards were compared to those admitted to non-dermatology wards. 26 The former patients were found to have a lower risk of readmission and a shortened hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding skin diseases and musculoskeletal diseases, men were more likely to be hospitalized urgently for the global categories, while women were more prone to unplanned hospitalization for skin infections in particular. Likewise, another study that analyzed dermatological hospitalizations in Spain between 2006 and 2016 registered more male patients, and 61% of hospitalizations were unplanned (Cuenca‐Barrales et al, 2021). Along the same lines, Patelarou et al (2016) found in a Greek sample that musculoskeletal and skin symptoms were more commonly recorded as a cause of emergency care in men, although we do not have data on whether they were hospitalized in the same proportion.…”
Section: Discussionmentioning
confidence: 99%